Improving the machinability of Ti-6A1-4V using innovate laser shock peened cemented carbide inserts - Lekam, Ofem Nweoyi (My University, 2019)
The effect of cutting tool composition manipulation and cutting edge laser modification for rapid heat dissipation during Ti-6Al-4V machining were investigated. Innovative cutting tool inserts produced by liquid phase sintering (LPS) and spark plasma sintering (SPS) were used for this research, and their effect during face milling of Ti-6Al-4V was investigated under the following process parameters: cutting speed ranged from 60 to 300 m/min, depth of cut from 0.5 to 1.5 mm at a constant feed/tooth of 0.1mm. Cutting insert performance was assessed in terms of flank wear, response to cutting force, temperature, and surface roughness. Composition manipulation with Mo2C (wt%) additions inhibited grain growth resulting in cutting tools with better combined mechanical properties. The inserts produced by LPS had higher fracture toughnesses (K1C) than their SPS counterparts. This was due to their larger and more uniformly distributed binder pools resulting from the formation of the liquid phase during LPS. On the other hand, the SPS inserts had smaller WC grains giving higher hardnesses. Laser peening (LP) of the cutting tool inserts slightly improved their mechanical properties. Notwithstanding, the LP inserts experienced rapid wear during face milling trials at higher depth of cut (1mm and 1.5mm) and speeds (100m/minute – 300m/minute). The introduction of ridges on the rake face of the cutting tool inserts improved upon their cutting performance and wear resistance. A clear relationship between the cutting tool hardness and workpiece surface roughness was established, with the Ti-6Al-4V workpieces surface roughness decreasing with increased cutting tool hardness. Furthermore, the inserts with higher hardness had better abrasive wear resistance
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy. October, 2019
Keywords: Lasers; Laser peening